Psychological health challenges and supportive care considerations for gynecological cancer patients during radiotherapy: a narrative review - Jun Ma; Xu Li; Xiu Yang; Muyi Zhang; Songbo Wu; Li Liu; Xueqian Ma; Panfeng Wang (Psycho-Oncologie, 2026)
Background: Gynecological cancer patients frequently experience anxiety, depression, and social isolation, particularly regarding body image, sexual health, fertility, and family roles. Radiotherapy is a central treatment modality and provides a clinically important window for psycho-oncological support. Objective: To synthesize evidence on psychological health challenges and supportive care considerations, including psychosocial interventions, for gynecological cancer patients during radiotherapy. Methods: We conducted a no-systematic narrative review with a structured literature search of PubMed/Medline and Scopus. Four core interventional studies (one randomized controlled trial and three interventional studies) and 54 (58 references cited in total) supporting references were synthesized according to a clinically derived thematic framework. Results: Gynecological cancer patients undergoing radiotherapy commonly experience moderate psychological distress before, during, and after treatment, with additional concerns related to pelvic side effects, sexual dysfunction, brachytherapy, and disrupted family roles. Core evidence indicates that nurse- and peer-led psycho-educational interventions may improve treatment readiness, and informational needs, but should not be interpreted as an evidence-based remedy for psychological distress reduction. Psychosocial interventions including cognitive behavioral therapy, stress management, and structured family support may improve quality of life, but benefits vary by intervention type, cancer subtype, and implementation context. Conclusions: Psychosocial interventions during gynecological cancer radiotherapy show promise but inconsistent benefit. Risk-adapted, radiotherapy-timed, and feasible multidisciplinary approaches are needed. Further high-quality trials are warranted.